Achieving responsible antimicrobial use: communicating with farmers. Issue 2 (3rd February 2017) - Reyher, Kristen K.; Barrett, David C.; Tisdall, David A.
Abstract : Communicating with farmers is key in achieving responsible antimicrobial use on the farm. With the farmer and vet working together and using their own individual knowledge and expertise, the change in antimicrobial use can be sustained and work for both parties. This article discusses the issues surrounding antimicribial use and why there may be a difference in opinion between the vet and the farmer. It provides tools that vets can use to improve their commmunication with the farmer to create a better working relationship.